On the modeling of the income distribution business cycle dynamics - Burkhard Heer (Center for Economic Studies and ifo Institute (CESifo), 2007)
Empirically, the income share is procyclical for the low-income groups and acyclical for the top 5%. We find that business cycle models should consider overlapping generations and elastic labor supply in order to replicate this finding.
Keywords: C68; D31; E32; 330; income distribution; business cycle; overlapping generations; Konjunkturtheorie; Overlapping Generations; Einkommensverteilung; Theorie; Welt